Implementation of 21st century learning in cultivating the value of global diversity at elementary school 109 Pekanbaru - Tiara Aulia Anggraini; Zaka Hadikusuma Ramadan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In the development of the 21st century, there are many changes and challenges that must be faced in life, one of which is in the educational field. It creates a new curriculum policy, an independent curriculum. The independent curriculum is designed as an attempt to develop the 21st century by strengthening the character of The Pancasila Student Profile, which is one of the global diversity characters. The research purpose of this paper is to describe the implementation, obstacles, and solutions for 21st -century learning in instilling global diversity values for fourth-grade students at SDN 109 Pekanbaru. The research method used is a qualitative descriptive method by collecting interview data, observing, and reviewing documentation.Data validity testing uses triangulation and data analysis uses the Miles and Huberman model, which are data reduction, data presentation, and conclusion drawing. The results indicate that the teachers have been maximized in implementing 21st-century learning in order to cultivate global diversity values for fourth-grade students properly based on the lesson plan. The teacher implemented it by developing critical thinking skills in understanding the surroundings and being able to solve problems, creatively creating something with new innovations, having verbal and written communication skills, and conducting collaborative learning. The four skills were developed in the learning process by the teacher gradually and sustainably.